The challenges of working with child sexual exploitation and how a psychoanalytic understanding can help - Bower, Marion; Solomon, Robin (Routledge, 2024)
"Sexual exploitation is becoming endemic in our society. It involves victims being coerced to enter abusive sexual relationships with individuals or gangs. It can occur with children from care homes - or from more privileged backgrounds. Sexual exploitation is so addictive that it is really difficult to extract the victims. This is the first book that we are aware of which examines Exploitation using a psychoanalytic framework which makes the behaviour and motives of victims and in some cases exploiters comprehensible. The book looks at a range of situations from care homes to refugee camps and elite schools. We expect this book to become indispensable for social workers, psychotherapists, counsellors and care workers who have to tackle child sexual exploitation. Giving up an addiction is a struggle. Our clinical examples show how much and what kinds of work are needed to start to release girls from their addiction to their exploiters. The roots of vulnerability lie in an attack on the maternal function. This is reflected in the huge expansion of day-care taking children from as little as three months old. Care for mothers and children can be transformed. We demonstrate how powerful properly organised maternal-type care can be, to give young people a sound start to their lives"--